Blowup Phenomena for the Compressible Euler and Euler-Poisson Equations with Initial Functional Conditions - Sen Wong; Manwai Yuen (The Scientific World Journal)
We study, in the radial symmetric case, the finite time life span of the compressible Euler or Euler-Poisson equations in RN. For time t≥0, we can define a functional H(t) associated with the solution of the equations and some testing function f. When the pressure function P of the governing equations is of the form P=Kργ, where ρ is the density function, K is a constant, and γ>1, we can show that the nontrivial C1 solutions with nonslip boundary condition will blow up in finite time if H(0) satisfies some initial functional conditions defined by the integrals of f. Examples of the testing functions include rN-1ln(r+1), rN-1er, rN-1(r3-3r2+3r+ε), rN-1sin((π/2)(r/R)), and rN-1sinh r. The corresponding blowup result for the 1-dimensional nonradial symmetric case is also given.